Rural Settlement in Iron Age Cessetania (Northeastern Iberian Peninsula). (20th January 2022) - Belarte, Maria Carme; Canela, Joan; Morer, Jordi; Cuscó, Oriol; Ocaña, Marc; Euba, Itxaso; Valenzuela-Lamas, Silvia
Abstract : Recent research has demonstrated the importance of rural settlement in the Iberian culture, although there are still few rural sites explored in depth. 'Rural settlement' is the term we use to designate the small habitation sites or agricultural structures that became common from the Middle Iberian Period (450–200 bc) onward; such sites constituted the basis of a hierarchical settlement system characteristic of societies developing towards archaic states. These settlements consist of one or two buildings together with silos and/or artisanal features. The main difficulty in studying such sites is their poor preservation. They are usually located on flat areas suitable for cultivation, and research has traditionally prioritised the study of larger sites. In this study, we revise the data from previous investigations in the territory of ancient Iberian Cessetania and present the results of recent research, paying particular attention to the Rabassats site. We compare these rural settlements to those in other nearby territories in the Iberian area as well as in the wider Mediterranean context. Detailed analyses of the remains of rural sites show a greater complexity than is often assumed and suggest that a variety of small settlements, from an economic and probably also from a social point of view, should be included under the generic heading of 'fourth order'.